Advances in electrochemical techniques for corrosion monitoring and laboratory corrosion measurements - Papavinasam, Sankara, 1962-; Rebak, Raúl B. 1956-; Yang, Lietai, 1958-; Berke, Neal Steven, 1952- (ASTM stock #STP1609, 2019)
"This compilation of Selected Technical Papers, STP1609, Advances in Electrochemical Techniques for Corrosion Monitoring and Laboratory Corrosion Measurements, contains peer-reviewed papers that were presented at a symposium held November 13-14, 2017, in Atlanta, Georgia, USA. The symposium was sponsored by ASTM International Committee G01 on Corrosion of Metals and Subcommittee G01.11 on Electrochemical Measurements in Corrosion Testing"--